2020
DOI: 10.1111/ced.14421
|View full text |Cite
|
Sign up to set email alerts
|

Recognizable vascular skin manifestations of SARS‐CoV‐2 (COVID‐19) infection are uncommon in patients with darker skin phototypes

Abstract: Reported cutaneous manifestations of SARS‐Cov‐2 infection include maculopapular rash, urticarial rash, varicelliform or vesicular lesions, petechiae/purpura, livedoid/necrotic lesions, chilblains‐like lesions (Covid toes), erythema multiforme‐like lesions, 1 and aphthous ulcers. 2 These cutaneous manifestations have been mostly reported from countries with Caucasian populations with a paucity of data from the skin‐of‐color populations. 3 We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 7 publications
1
27
1
2
Order By: Relevance
“… [ 331 ] Pernio-like eruption 4 M, 3 F 33 Topical/oral glucocorticoids or none [ 332 ] Chilblain-like lesions M 10 Topical glucocorticoids [ 333 ] Acral lesions 4 F, 1 M 3 None [ 334 ] Vascular lesions 3 F, 7 M 39.9 N.A. [ 335 ] Macular eruption with vasculitis F 81 None [ 336 ] Maculopapular rash 3 F, 1 M 21.75 Hydrocortisone, rupatadine and none [ 337 ] Ulcers 3 M 65.6 Antibiotics [ 338 ] Livedo racemosa and retiform purpura 4 55 Anticoagulation therapy [ 339 ] Enanthem 6 50 N.A. [ 340 ] Erythema nodosum M 42 Topical glucocorticoids [ 341 ...…”
Section: Resultsmentioning
confidence: 99%
“… [ 331 ] Pernio-like eruption 4 M, 3 F 33 Topical/oral glucocorticoids or none [ 332 ] Chilblain-like lesions M 10 Topical glucocorticoids [ 333 ] Acral lesions 4 F, 1 M 3 None [ 334 ] Vascular lesions 3 F, 7 M 39.9 N.A. [ 335 ] Macular eruption with vasculitis F 81 None [ 336 ] Maculopapular rash 3 F, 1 M 21.75 Hydrocortisone, rupatadine and none [ 337 ] Ulcers 3 M 65.6 Antibiotics [ 338 ] Livedo racemosa and retiform purpura 4 55 Anticoagulation therapy [ 339 ] Enanthem 6 50 N.A. [ 340 ] Erythema nodosum M 42 Topical glucocorticoids [ 341 ...…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to consider that our dataset is composed of lesions on both white and dark skin. As of yet, very few case studies have reported skin lesions in COVID‐19 patients from the Indian subcontinent 6,7 . This work was constrained by the small number of images of COVID‐19 lesions from skin‐of‐color populations, used for training as well as for validation and the model is likely biased towards white skin (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the first study to draw attention to skin lesions, nearly 20.4% (18 of 88) of patients, with a confirmed diagnosis of COVID‐19, developed cutaneous manifestations 4 . This number contrasts with 0.2%, 7.25%, and 12.7% of cases that developed skin abnormalities in a study from China and two studies from India, respectively 5‐7 . Subsequently, various reports of skin manifestations in both adults (with severe forms of COVID‐19) and younger paucisymptomatic patients have been published 8,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously published a lack of such pernio-like diagnoses in 5635 patients treated by dermatology between March and June 2020 in a minority-predominant safety-net hospital system in New York City. 4 Pangti et al 5 similarly reported that cutaneous manifestations were uncommon in pigmented skin in a series of 138 patients with confirmed COVID-19 diagnoses. Given that the study by Pangti et al 5 was performed in India by Indian dermatologists and the one by Avancini et al 1 in Brazil by Brazilian dermatologists, it is likely they did not have inadequate training in skin of color.…”
mentioning
confidence: 95%